Meta-analyses of genes modulating intracellular T3 bio-availability reveal a possible role for the DIO3 gene in osteoarthritis susceptibility. Issue 1 (19th August 2010) - Meulenbelt, Ingrid; Bos, Steffan D; Chapman, Kay; van der Breggen, Ruud; Houwing-Duistermaat, Jeanine J; Kremer, Dennis; Kloppenburg, Margreet; Carr, Andrew; Tsezou, Aspasia; González, Antonio; Loughlin, John; Slagboom, P Eline
Abstract : Objective: To study whether common genetic variants of the genes involved in the complex regulatory mechanism determining the intracellular bio-availability of T3 influence osteoarthritis onset. Methods: In total 17 genetic variants within the genes encoding WD40-repeat/SOCS-box protein 1, ubiquitin specific protease 33, thyroid hormone receptor α, deiodinase, iodothyronine, type III ( DIO3 ) and Indian hedgehog were measured and associated with osteoarthritis in a meta-analyses in European populations from the UK, The Netherlands, Greece and Spain containing a total of 3252 osteoarthritis cases and 2132 controls. Results: The minor allele of the DIO3 variant rs945006 showed suggestive evidence for protective association in the overall meta-analyses, which was supported by individual osteoarthritis studies and osteoarthritis subtypes. The association appeared most significant in cases with knee and/or hip with an allelic OR of 0.81 (95% CI 0.70 to 0.930) with a nominal p value of 0.004 and a permutation-based corrected p value for multiple testing of 0.039. Conclusion: The findings suggest that the DIO3 gene modulates osteoarthritis disease risk; however, additional studies are necessary to replicate our findings. To elucidate the molecular mechanisms focus should be on the local adaptation to T3 availability either during the endochondral ossification process or during ageing of the articular cartilage.